2002
DOI: 10.1159/000063018
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of avian microchromosomes

Abstract: The origin of avian microchromosomes has long been the subject of much speculation and debate. Microchromosomes are a universal characteristic of all avian species and many reptilian karyotypes. The typical avian karyotype contains about 40 pairs of chromosomes and usually 30 pairs of small to tiny microchromosomes. This characteristic karyotype probably evolved 100–250 million years ago. Once the microchromosomes were thought to be a non-essential component of the avian genome. Recent work has shown that even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
265
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(286 citation statements)
references
References 54 publications
16
265
0
5
Order By: Relevance
“…ACA has a few microchromosomes that are conserved between ACA and GGA, and that may have arisen in the reptile ancestor [11]. It is suggested that the formation of microchromosomes leads to a reduction of genome size [23]. We find that TSC and CNI genome sizes are closer to GGA than to ACA, and total GC content in GGA, TSC and CNI is higher than in ACA (figure 2b).…”
Section: Discussionmentioning
confidence: 67%
“…ACA has a few microchromosomes that are conserved between ACA and GGA, and that may have arisen in the reptile ancestor [11]. It is suggested that the formation of microchromosomes leads to a reduction of genome size [23]. We find that TSC and CNI genome sizes are closer to GGA than to ACA, and total GC content in GGA, TSC and CNI is higher than in ACA (figure 2b).…”
Section: Discussionmentioning
confidence: 67%
“…This reasoning assumes that f is a precise estimate of selectable autozygosity. However, the simulation results suggest that individuals within an inbreeding class can vary widely in autozygosity even when the number of linkage groups is large, as is thought to be the case in birds (Thorneycroft, 1975;Burt, 2002). Therefore, some of the variation in fitness due to heterosis that is not accounted for by f may be reflected in H. If so, then SSR HFC's within inbreeding classes may be due to variation among identically inbred individuals in true autozygosity, rather than a result of local effects.…”
Section: Genomic Aspects Of Hfcsmentioning
confidence: 94%
“…Although physical linkage groups in birds are likely to be small and numerous (Burt, 2002), bottlenecks and population structure can increase the level of linkage disequilibrium (Hansson and Westerberg, 2002), and perhaps falsely give the impression of local effects because each marker locus would represent a substantial portion of the genome. Thus, the general effects hypothesis can be rejected only after the variance in individual autozygosity for a known level of inbreeding has been accounted for (cf.…”
Section: Genomic Aspects Of Hfcsmentioning
confidence: 99%
“…However, the karyotype of the common ancestor of extant sauropsids is thought to have contained both macrochromosomes and microchromosomes (Burt 2002;Norris et al 2004), although some lineages underwent frequent secondary fusion of microchromosomes resulting in no or few microchromosomes as seen in the reptilian family Crocodylidae and the avian family Falconiformes (Cohen & Gans 1970;De Boer & Sinoo 1984). In contrast, chromosome sizes are relatively uniform and there is no striking bias in inter-chromosomal GC-content in most mammals.…”
Section: Insight Into the Evolutionary History Of Intra-genome Gc Hetmentioning
confidence: 99%
“…Although the evolutionary origin and intrinsic nature of this GC heterogeneity is not fully understood (Eyre-Walker & Hurst 2001), the existence of intra-genome GC Karyotypes of extant sauropsids (reptiles and birds) generally consist of two major components: macrochromosomes and microchromosomes (Burt 2002;Norris et al 2004). In chicken, cytogenetic observations indicate that microchromosomes exhibit a higher gene density (McQueen et al 1998;Smith et al 2000), a higher density of CpG islands (McQueen et al 1996) and a higher GC-content than macrochromosomes (Auer et al 1987;Andreozzi et al 2001).…”
Section: Introductionmentioning
confidence: 99%